Diklat Instalasi Listrik Aliran Atas Untuk Meningkatkan Dasar Orientasi Perkeretaapian di BTP Kelas II Palembang - Arifianto, Teguh; Pradipta, Andri; Arifidin, M. Afif Amalul; Sunaryo, Sunaryo; Moonlight, Lady Silk; Puspitarini, Erri Wahyu (Jurnal Pengabdian Literasi Digital Indonesia, 2024)
This community service activity is focused on the implementation of education and training on high-flow electrical installations by utilizing lecture and discussion methods. This training is organized systematically to provide participants with an in-depth understanding of the technical and safety aspects of overhead electrical installations. The overhead electrical installation is one of the important components in the railway system. This activity aims to improve basic understanding of railway orientation, especially related to overhead electrical installations. This activity was carried out online through the zoom application on May 21, 2024 and was attended by participants from the Balai Teknik Perkeretaapian Kelas II Palembang. Participants showed high enthusiasm during the training. This can be seen from the participants' activeness in discussion and question and answer sessions. The tangible results of this community service activity show an increase in participants' understanding of overhead electrical installations which is reflected in the post-training evaluation. The knowledge gained during this activity is expected to be applied in daily work activities in each participant's duty area to support improved performance and operational safety in the railway sector.